2004
DOI: 10.1165/rcmb.2004-0161oc
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid and Cytokines Synergistically Enhance Toll-Like Receptor 2 Expression in Respiratory Epithelial Cells

Abstract: Respiratory epithelial cells play important roles not only in host defense mechanisms, but also in inflammatory responses. Inhaled corticosteroids are widely used for the treatment of patients with inflammatory lung disorders, including asthma, chronic obstructive pulmonary disease, and sarcoidosis. Corticosteroids effectively reduce the production of inflammatory mediators, such as cytokines and chemokines. Although these molecules are also essential for host defense responses, there is no convincing evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 37 publications
6
96
0
4
Order By: Relevance
“…In the same way, responsiveness to the Grampositive bacterium S. aureus could be induced by transfection of TLR2 and TLR2/CD36, thus paralleling the findings with LTA. Moreover, it has been reported that TNF-␣ and IFN-␥ increase expression of TLR2 in respiratory epithelial cells (30). Indeed, we observed that prestimulation of BEAS-2B cells with a combination of these both cytokines increased TLR2 mRNA expression (Fig.…”
Section: Expression Levels Of Tlr2 and Coreceptors Regulate Sensitivisupporting
confidence: 59%
“…In the same way, responsiveness to the Grampositive bacterium S. aureus could be induced by transfection of TLR2 and TLR2/CD36, thus paralleling the findings with LTA. Moreover, it has been reported that TNF-␣ and IFN-␥ increase expression of TLR2 in respiratory epithelial cells (30). Indeed, we observed that prestimulation of BEAS-2B cells with a combination of these both cytokines increased TLR2 mRNA expression (Fig.…”
Section: Expression Levels Of Tlr2 and Coreceptors Regulate Sensitivisupporting
confidence: 59%
“…In fact, genetic complementation experiments with human TLR7 and TLR8 suggest that TLR8, not TLR7, is responsible for the recognition of single-stranded RNA in humans (41). Moreover, TLR7 and TLR8 are not expressed in human bronchial epithelial cells (44), and our experiments using a vector encoding a dominant-negative form of MyD88 rule out a role for those receptors in the activation of influenza A-infected human epithelial cells. Indeed, it was established that MyD88 is essential for the signaling downstream from TLR7 and TLR8 (41)(42)(43)45).…”
Section: Tlr3 Signaling and Respiratory Epithelial Cell Activationmentioning
confidence: 65%
“…In contrast, the activation of IRF-3 induces production of type I IFN and induces an anti-viral response. Airway epithelial cells have been shown to express mainly TLR2-6 [4,5]. TLR2, which is heterodimerized with TLR1 or TLR6, recognizes bacterial components such as lipoprotein, peptidoglycan (PGN) and lipoteichoic acid, GPI anchor from protozoa and some viral envelope proteins such as those expressed by measles virus and human cytomegalovirus.…”
Section: Epithelium and Innate Immune Recognitionmentioning
confidence: 99%
“…Expression of the type I IFN, IFN-β, and type III IFNs, IFN-λ1 (IL-29) and IFN-λ2/3 (IL-28A/B), is important in the antiviral response of the epithelium. TLR3 and RNA helicases are important sensors for detection of viral infection and induce production of IFN-β and IFN-λ in epithelial cells [4][5][6][7]. Type II IFN, IFN-γ, which is produced from activated T cells and NK cells, also activates IFN-λ production in epithelial cells, probably amplifying the antiviral effects of specific T cells.…”
Section: Epithelium and Host Defensementioning
confidence: 99%